The Mediating Role of Job Satisfaction on Training and Compensation on Employee Performance PT. Micro Madani Institute - Ayu, Chintya Puteri; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Analyzing training affects employee job satisfaction, compensation affects employee job satisfaction, training affects work performance, compensation affects employee work performance, employee job satisfaction affects work performance training affects performance through employee job satisfaction, compensation affects work performance through employee job satisfaction. Quantitative research using PLS4 to measure Likert scale. Samples are 101 PT Micro Madani employees. The results are training has significant effect on job satisfaction, compensation has significant effect on job satisfaction, training has no significant effect on performance, compensation has significant effect on performance, job satisfaction has significant effect on performance, training has no significant effect on performance through job satisfaction as an intervening, compensation has significant effect on performance through job satisfaction as an intervening